An investigation into the relationship between electrochemical properties and flotation of sulphide minerals - Chimonyo, Wonder (Centre for Minerals Research, 2016)
There is a growing importance in the mineral processing industry to find ways which are economic and effective in improving the recovery of minerals in the flotation process. The focus of this study was on the recovery by flotation of minerals found in the Merensky reef, which is one of the major reefs in the Bushveld complex. In that reef, base metal sulphide (BMS) minerals are commonly associated with PGMs and this has an effect on the way in which these minerals are concentrated by flotation (Vermaak et al. 2004; Wiese et al. 2005b; Miller et al. 2005; Schouwstra et al. 2000).A major problem in this process has been reported to be losses of valuable minerals (PGMs) associated with the loss of BMS (Wiese et al. 2005b), during flotation. The present investigation has focused on studying the relationship between the flotation of sulphide minerals using xanthates as collectors and the electrochemical properties of the flotation system. It is well known that electrochemical mechanisms in flotation systems have a major influence on flotation since the reactions occurring at the mineral/solution interface are of critical importance in the process (Woods, 1971).The aim of this study was to investigate the extent to which there was a relationship between the electrochemical reactions occurring in this ore which could indicate the effectiveness of the flotation process. The electrochemical reactions were studied by determining the redox potential changes occurring when various changes were made. These were the length of the alkyl chain length of the xanthate collector, changing the pH or using various chemical reagents to change the potential of the system. It was found from the rest potential measurements, that collectors of different chain length have different extents of interaction with mineral surface. A greater interaction, which is indicated by a greater change in the mixed potential after addition of the collector, is considered to be indicative of a greater adsorption of the collector at the mineral surface. It was hypothesized that this stronger adsorption by collectors of longer alkyl chain length would result in improved flotation performance. However, this was not observed to be the case and that was consistent with previous results on the relationship between the recovery of sulphide minerals in the Merensky ore and xanthates of different chain lengths. Thus it was shown that there was no correlation between the interactions between collectors of different alkyl chain lengths as determined through electrochemical studies and the flotation performance of valuable minerals under the tests conditions used.